Variation of effect estimates in the analysis of mortality and length of hospital stay in patients with infections caused by bacteria-producing extended-spectrum beta-lactamases: a systematic review and meta-analysis. Issue 1 (20th January 2020) - Shamsrizi, Parichehr; Gladstone, Beryl Primrose; Carrara, Elena; Luise, Dora; Cona, Andrea; Bovo, Chiara; Tacconelli, Evelina
Abstract : Objective: To assess the variation of effect estimates in the analysis of mortality and length of stay (LOS) in patients with infections caused by extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae . Design: Systematic review and meta-analysis Methods: Literature search for clinical studies from 1 January 1960 to 1 October 2018 was conducted in PubMed. Primary outcomes were risk ratios (RRs) of all-cause and attributable mortality and weighted mean differences (WMDs) in LOS in patients with bloodstream infections (BSIs) and non-invasive infections. Any change in the effect estimates was assessed by grouping studies according to design, setting, economy-based country classification, reporting period, microbiological aetiology, infection type and adjustment for appropriateness of empirical treatment. The impact of ESBL production was calculated using random-effect meta-analysis and heterogeneity was evaluated by I 2 statistics and metaregression. Results: Eighty-four studies including 22 030 patients and 149 outcome measures were included in the meta-analysis. Most studies were retrospective cohorts from high-income countries, providing unadjusted estimates. ESBL production in patients with BSIs (56 studies) increased the RR for all-cause mortality by a factor of 1.70 (95% CI 1.52 to 1.90; p<0.001), attributable mortality (16 studies) by 1.75 (95% CI 1.448 to 2.108; p<0.001) and WMD in the intensive care unit by 3.07 days (95% CI 1.61 to 4.54; p<0.001). WMD in hospital LOS was significantly higher in BSIs (4.41 days; 95% CI 3.37 to 5.46; p<0.001) and non-invasive (2.19 days; 95% CI 1.56 to 2.81; p<0.001). Subgroup analyses showed variation of estimates by study design, population, strain and assessment of appropriateness of empiric treatment. High heterogeneity was observed in all analyses. Conclusions: Current evidence of the clinical burden of infections caused by ESBL-producing bacteria is highly heterogeneous and based mainly on unadjusted estimates derived from retrospective studies. Despite these limitations, ESBL production in strains causing BSIs seems associated with higher all-cause and attributable mortality and longer hospitalisation.